2019
DOI: 10.1080/19420862.2019.1599634
|View full text |Cite
|
Sign up to set email alerts
|

Process optimization and protein engineering mitigated manufacturing challenges of a monoclonal antibody with liquid-liquid phase separation issue by disrupting inter-molecule electrostatic interactions

Abstract: We report a case study in which liquid-liquid phase separation (LLPS) negatively impacted the downstream manufacturability of a therapeutic mAb. Process parameter optimization partially mitigated the LLPS, but limitations remained for large-scale manufacturing. Electrostatic interaction driven selfassociations and the resulting formation of high-order complexes are established critical properties that led to LLPS. Through chain swapping substitutions with a well-behaved antibody and subsequent study of their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
(72 reference statements)
2
11
0
Order By: Relevance
“…To achieve that conditions under which LLPS occurs must first be identified for each individual mAb. While the primary sequence of some mAbs may render them inherently more prone to self-association and LLPS, 25,38 a wide variety of additives, such as salts, macromolecular crowders and polyvalent ions, [39][40][41] can be used alongside temperature and pH to induce LLPS. Selection of these additives and conditions could be achieved using conventional highthroughput screening platforms, for example, through detection of opalescence by light scattering techniques.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve that conditions under which LLPS occurs must first be identified for each individual mAb. While the primary sequence of some mAbs may render them inherently more prone to self-association and LLPS, 25,38 a wide variety of additives, such as salts, macromolecular crowders and polyvalent ions, [39][40][41] can be used alongside temperature and pH to induce LLPS. Selection of these additives and conditions could be achieved using conventional highthroughput screening platforms, for example, through detection of opalescence by light scattering techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Gentiluomo et al [ 34 ] characterized the native reversible self-association of mAbs using Fab and Fc fragments and confirmed that self-associations such as hydrophobic and electrostatic interactions are driven by the Fab fragment. In addition, Du et al [ 24 ] and Chow et al [ 25 ] identified the amino acids responsible for the LLPS propensity of mAbs, located in the Fab region. In this study, we calculated Fab dipole moments to investigate the Fab–dipole-related association.…”
Section: Discussionmentioning
confidence: 99%
“…The effective in silico design of mAbs has previously been reported to reduce the risk of viscosity escalation [ 19 23 ]. In terms of LLPS, Du et al [ 24 ] successfully used in silico homology modelling and charged patch analysis to identify seven amino acids that were potentially related to self-association. They confirmed that mutations of the amino acids resulted in a lower LLPS propensity.…”
Section: Introductionmentioning
confidence: 99%
“…One specific result of increased self-association on formulation stability and manufacturing processes is thermodynamically driven liquid-liquid phase separation (LLPS) [ 146 ]. The formation of a protein-rich bottom layer and protein-depleted top layer, characteristic of LLPS, typically occurs for highly concentrated solutions at low temperatures (2–8 °C), such as refrigerated formulations [ 147 ]. It can also occur during large-scale purification in which intermediates are kept either at room temperature or 2–8 °C for extended periods of time.…”
Section: Self-association and High Concentration Propertiesmentioning
confidence: 99%
“…Therefore, it would be desirable to minimize LLPS with early-stage property engineering. Recent work has used protein engineering to investigate the mechanistic foundations of antibody site-specific contributions to LLPS behavior [ 147 ]. One study found that strong self-association between the light chains of a mAb contributed to electrostatic interactions resulting in LLPS.…”
Section: Self-association and High Concentration Propertiesmentioning
confidence: 99%